Oral hygiene assessment by school teachers and peer leaders using simplified method - Haleem, Abdul; Siddiqui, Muhammad Irfanullah; Khan, Ayyaz Ali (International Journal of Health Sciences, 2012)
Background: A significant proportion of children in developing countries are having plaque-induced gingivitis. A public health strategy may involve teachers and peer leaders to motivate and train school children for regular and thorough removal of dental plaque. The monitoring and evaluation of such a strategy may require teachers and peer leaders to assess oral hygiene status of children at periodic intervals. Objective: To validate the simplified dental examination performed by teachers and peer leaders to detect dental plaque and calculus. Methodology: This longitudinal study involved 632 adolescents studying in sixteen schools of Karachi, Pakistan. Eight schools each were randomly allocated to the peer-led and teacher-led strategies of examination. One section of class six was selected at random in each school to be included in the study. In each selected section of class six the trained teacher-in-charge or a peer-leader undertook dental examinations at baseline, 6-month and 18-month intervals and their findings were compared with those of a dentist. The outcome measures included the Kappa values for examiner agreement as well as the sensitivity, specificity, positive and negative predictive values. Results: All teachers and peer leaders showed a substantial degree of agreement (Kappa ≥ 0.8) with the dentist in detecting plaque and calculus at all three examinations. The values of validity measures for teachers’ and peer leaders’ examination were in the range of 87-90%. Conclusions: The examinations performed by teachers and peer leaders were reasonably valid to detect plaque and calculus. However, booster training sessions are needed to maintain their performance as dental examiners. Key words: Validity, teachers, peers, oral examination, dental examination, plaque, calculus.